Pengaruh Latihan Meditasi Terhadap Perkembangan Kejiwaan Dan Kecerdasan Anak-Anak - Willie Japaries; Suminah Suminah; Stella Maris Bakara; Frisca Desma Ayu; Shally Joncicilia (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2023)
Background: Meditation practice has been widely known in Indonesia and abroad. Initially it was practised by adults. Later on, meditation is also practised by children as it brings significant benefit for their growth and development of mind and personality. Methods: This study is a systematic review of published articles on data base of PubMed, Researchgate, CNKI, about effects of meditation for children, within the last 10 years. Results: From dozens of clinical studies reported in scientific journals, it is apparent that meditation can be practised by healthy children, children with ADHD and diseases. In general, meditation practice brings positive effects for children and their parents.. Conclusion: Meditation practice is safe and effective for children to bring benefit for their growth and development of mind and personality.